Evolution of Glucose Tolerance After Treatment of Acromegaly: A Study in 57 Patients - Jonas, C.; Maiter, D.; Alexopoulou, O. (Hormone and Metabolic Research, 2016)
The aim of our study was to evaluate the evolution of glucose metabolism in 57 patients after treatment of their acromegaly and to determine risk factors for the persistence of abnormal glucose tolerance. Therefore, we performed IGF-I measurements, oral glucose tolerance tests (OGTTs), and HOMA to evaluate insulin sensitivity (HOMA-S) and β-cell function (HOMA-β) at diagnosis and at last visit (median follow-up 7 years). At diagnosis of acromegaly, 14 patients (25%) were diabetic and 15 (26%) had impaired glucose tolerance, whereas at the last visit, 32% were diabetic and 26% remained glucose intolerant. There was a decrease in fasting glucose (median − 7.0 mg/dl) in the 20 patients cured by surgery, whereas it increased in the 28 patients controlled under medical therapy (median + 2.0 mg/dl; p<0.05 vs. cured group) and in the 9 patients with active disease (median + 4.0 mg/dl). Loss of β-cell function was more pronounced in the patients under medical treatment (median − 87.9%) vs. the cured group (median − 30.4%; p<0.05). There was a decrease in HbA1c between diagnosis and last visit in patients under pegvisomant (mean − 19.2 mmol/mol) vs. a small increase in patient treated by somatostatin analogues (+ 3.4 mmol/mol; p<0.05). Independent risk factors for persistent abnormal glucose tolerance were the glucose tolerance status at diagnosis and ongoing treatment with somatostatin analogues. In conclusion, we found that more than 50% of patients still have IGT or diabetes after treatment of acromegaly. Improvement of glucose metabolism is mainly observed in cured patients and in patients treated with pegvisomant.
Keywords: acromegaly; insulin-growth factor-I; growth hormone; diabetes; glucose; HOMA; OGTT